Suicides and Factors Associated With Suicides-A Study in a Rural Setup of Pondicherry in South India - Bharatwaj, R.S (Journal of Brain Sciences, 2015)
The aim of this study was to find out the suicide rate and possible factors associated with suicides in a rural area in Pondicherry. Information was collected regarding suicides within the last two years, using a pretested questionnaire by house to house survey in the study area which is a rural set up in the south Indian union territory of Pondicherry. We found that the annual average suicide rate in this village was 110.64/100,000 population which is very high compared to the national average. The majority of suicides were committed by married males (75%). Commonest age of suicide is 15-45 years (46.16%). The reasons found for suicide were family problems leading to stress 9(78.84%) and health problems 4(30.76%). The commonest mode of suicide was by hanging 6(46.15%) and least by burning 3(23.07%). Maximum suicide occurred in the month of November to December 4(36.36%). The findings imply the need for a holistic community based approach to tackle this complex issue of suicide.